2022
DOI: 10.2340/actadv.v102.1123
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia Cutis: Clinical Features and Outcomes of 56 Patients

Abstract: Leukaemia is a malignant neoplasm of the haematopoietic system. Cutaneous manifestations of leukaemia are called leukaemia cutis, and are regarded as a sign of poorer prognosis and shorter survival time. A single-institution retrospective review was performed of medical records of patients diagnosed with leukaemia cutis in the dermatology department of Seoul St Mary’s Hospital between January 2012 and April 2021. Fifty-six cases with cutaneous leukaemic involvement and underlying haematological malignancy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“… 10 Another recent retrospective review observing patients with leukemia between 2012 and 2021 concluded that 84% of patients diagnosed with leukemia cutis ultimately died. 11 Of the patients who died, 93% died within 10 months of their diagnosis of leukemia cutis. 11 These findings are consistent with our patient who died within one month of her diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 Another recent retrospective review observing patients with leukemia between 2012 and 2021 concluded that 84% of patients diagnosed with leukemia cutis ultimately died. 11 Of the patients who died, 93% died within 10 months of their diagnosis of leukemia cutis. 11 These findings are consistent with our patient who died within one month of her diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Of the patients who died, 93% died within 10 months of their diagnosis of leukemia cutis. 11 These findings are consistent with our patient who died within one month of her diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 The rare cases that occur before bone marrow or peripheral blood involvement, whose systemic involvement may take months to years to appear, are called aleukemic leukemias. 9 , 10 …”
Section: Specific Skin Lesions Secondary To Systemic Hematologic Mali...mentioning
confidence: 99%
“…Considering the different types of leukemias, a prevalence of LC of 10% to 15% is observed in AML, 2 , 3 , 8 , 9 of which the myelomonocytic (AMML) and monocytic (MoAL) subtypes are the most affected, in up to half of the cases. 2 , 5 , 6 In CLL, the most common presentation of systemic leukemias, LC is reported in 4% to 27% of these cases, 3 , 15 , 16 more frequently in the Richter’s syndrome, which is the rare transformation of CLL into a large cell lymphoma.…”
Section: Specific Skin Lesions Secondary To Systemic Hematologic Mali...mentioning
confidence: 99%